Response of Extreme Rainfall for Landfalling Tropical Cyclones Undergoing Extratropical Transition to Projected Climate Change: Hurricane Irene (2011). Issue 3 (3rd March 2020) - Liu, M.; Yang, L.; Smith, J. A.; Vecchi, G. A.
Abstract: Extreme rainfall and flooding associated with landfalling tropical cyclones (TCs) have large societal impacts, both in fatalities and economic losses. This study examines the response of TC rainfall to climate change projected under future anthropogenic greenhouse emissions, focusing on Hurricane Irene, which produced severe flooding across the Northeastern United States in August 2011. Numerical simulations are made with the Weather Research and Forecasting model, placing Irene in the present‐day climate and one projected for the end of 21st century climate represented by Phase 5 of the Coupled Model Intercomparison Project Representative Concentration Pathway 8.5 scenario. Projected future changes to surface and atmospheric temperature lead to a storm rainfall increase of 32% relative to the control run, exceeding the rate expected by the Clausius‐Clapeyron relation given a ~3‐K lower atmospheric warming. Analyses of the atmospheric water balance highlight contributions to the increase in rainfall rate from both increased circulation strength and atmospheric moisture. Storm rainfall rate shows contrasting response to global warming during TC and extratropical transition periods. During the TC phase, Irene shows a significant increase of storm rainfall rate in inner core regions. This increase shifts to outer rainbands as Irene undergoes extratropical transition, collocated with the maximum tangential wind increase and the change of secondary circulation strength. Changes of storm track from the control run to global warming projections play a role in the change of spatial rainfall pattern. Distinct roles of surface and atmospheric warming in storm rainfall and structure changes are also examined. Plain Language Summary: Landfalling tropical cyclones (TCs) can undergo the process of extratropical transition, through which storm structure and dynamics transform, enabling them to persist (and extend their hazards) to middle‐ and high‐latitude regions, which have large‐scale conditions hostile to TCs. These so‐called post‐TCs can produce enhanced rainfall relative to typical TCs, leading to more severe flood hazards. For example, Hurricane Irene (2011) produced extreme flooding along the East Coast of the United States and Canada, especially in mid‐Atlantic regions and New England. Future changes of post‐TCs have strong implications for flood risk assessment and management. To provide new insights on this issue, we conducted a case study focusing on Hurricane Irene (2011) by placing Irene in a projected warmer climate, which allows us to examine aspects of the influence of climate change on future storm rainfall rate. Irene produced heavier rainfall in a warming climate than the current climate. This increase is mainly concentrated in the inner core region at the TC phase and shifts to outer regions at the post‐TC phase. The magnitude of Irene rainfall rate increase exceeds the rate of water vapor increase under the warmer climate, highlighting increased flood risk in the future. Key Points: Increase of Irene rain rate is observed in inner core regions for tropical cyclone phase but in outer rainbands during transition period Increase of Irene rain rate exceeds the rate of water vapor increase in a warming climate, suggesting the importance of dynamical effects